Sturge weber syndrome: A case report - Mitesh Karn; Aachal Barma; Liladhar Ojha; Suman Bhatta; Puja Neupane; Kusum Dhital; Anjan Sharma; Suraj Acharya; K. C. Unika; Asmita Barma; Devraj Mahato; Gunjana Rawal (Clinical Case Reports)
Key Clinical Message This report presents a 14‐year‐old male with seizures and facial port‐wine stains, who upon further evaluation was found to have SWS. Early diagnosis and consistent treatment of Sturge–Weber syndrome in children are essential to prevent seizures and improve quality of life. Anti‐seizure medications play a crucial role in preventing and controlling seizures.